Analysis of Cost Control, Working Capital Turnover, and Economic Profitability at PT Sampoerna Agro Tbk - Nabila, Harris Rahma (International Journal of Community Service & Engagement, 2024)
This research aims to analyze the level of cost control ratio, working capital turnover and economic profitability at the company PT Sampoerna Agro Tbk. Financial report data from 2015 to 2019 was collected using documentation techniques. Data were analyzed using a descriptive approach. Research findings prove that from 2015 to 2019 the cost control ratio was categorized as efficient with an average of 33.41% and was above the industry average. However, in the same period, the working capital turnover ratio and economic profitability ratio respectively averaged 2.994 and 5.64% and were categorized as unfavorable because they were below the industry average.